Aplicación del proceso contable de la empresa comercial “Ferretería Darío” del cantón Huaquillas-periodo julio 2013 - Honores Montalván, Carmen Julia (2015)
This research work title: APPLICATION PROCESS ACCOUNTING BUSINESS ENTERPRISE "HARDWARE DARÍO" CANTON HUAQUILLAS PERIOD JULY 2013 was made based on the standards set by the National University of Loja, mode Schooling, in compliance to pre obtaining of engineering degree in Accounting and Auditing requirements. To comply with the objectives, began with gathering information Hardware Darius, it served to consolidate the accounting records. And then to develop a plan requiring the company accounts and learn about the development of their business and begin to organize the accounting process from the initial inventory to obtain the financial statements, information was collected through the sales receipts and Latches for systematization, analysis and processing of data that allows the collection of accurate and timely information. It is concluded that applying an accounting process based on accounting and tax rules real and timely financial statements as far as the owner is recommended to take into account obtained the information submitted, and the benefit of the application of the accounting process to benefit from the rules tax regulations for you to know the actual economic situation of your company